2018
DOI: 10.1371/journal.pcbi.1005993
|View full text |Cite
|
Sign up to set email alerts
|

Automated plant species identification—Trends and future directions

Abstract: Current rates of species loss triggered numerous attempts to protect and conserve biodiversity. Species conservation, however, requires species identification skills, a competence obtained through intensive training and experience. Field researchers, land managers, educators, civil servants, and the interested public would greatly benefit from accessible, up-to-date tools automating the process of species identification. Currently, relevant technologies, such as digital cameras, mobile devices, and remote acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(186 citation statements)
references
References 65 publications
2
156
0
5
Order By: Relevance
“…Automated approaches, such as computer vision and machine learning methods, can complement valuable citizen science data and may help bridge the “annotation gap” (Unger et al., ) between existing data and research‐ready data sets. Deep learning approaches, in particular, have been recently shown to achieve impressive performance on a variety of predictive tasks such as species identification (Joly et al., ; Wäldchen et al., ), plant trait recognition (Younis et al., ), plant species distribution modeling (Botella et al., ), and weed detection (Milioto et al., ). Carranza‐Rojas et al.…”
mentioning
confidence: 99%
“…Automated approaches, such as computer vision and machine learning methods, can complement valuable citizen science data and may help bridge the “annotation gap” (Unger et al., ) between existing data and research‐ready data sets. Deep learning approaches, in particular, have been recently shown to achieve impressive performance on a variety of predictive tasks such as species identification (Joly et al., ; Wäldchen et al., ), plant trait recognition (Younis et al., ), plant species distribution modeling (Botella et al., ), and weed detection (Milioto et al., ). Carranza‐Rojas et al.…”
mentioning
confidence: 99%
“…Research in this subject should be continued, and even though DL still has some obstacles to overcome (Marcus 2018), it has already advanced a lot (Guo et al 2016; Wäldchen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is also common practice that deep neural networks outperform shallow neural networks (Chatfield et al 2014). In recent years, CNN technology has advanced greatly (LeCun et al 2015; Mishkin et al 2017; Wäldchen et al 2018), and many biological relevant studies have shown promising results (as can be read in the next Section: Related deep learning studies).…”
Section: Deep Learningmentioning
confidence: 99%
“…In contrast, automated mammal and fish identification are done by taking images under field site condition (Weinstein, ). Automated plant identification is required under field as well as under lab conditions (Wäldchen, Rzanny, Seeland, & Mäder, ).…”
Section: Recent Research Studies Using Deep Learning For Species Idenmentioning
confidence: 99%